2008
DOI: 10.1016/j.bios.2007.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cell adhesion and spreading on impedance characteristics of cell-based sensors

Abstract: Impedance measurements of cell-based sensors are a primary characterization route for detection and analysis of cellular responses to chemical and biological agents in real time. The detection sensitivity and limitation depend on sensor impedance characteristics and thus on cell patterning techniques. This study introduces a cell patterning approach to bind cells on microarrays of gold electrodes and demonstrates that single-cell patterning can substantially improve impedance characteristics of cell-based sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…These equivalent circuits have been used to model different types of cells on IMEs or other microelectrodes and for analysis of different impedance components (Ehret et al 1997;). Certainly, microelectrode-based systems for cell attachment could be modeled by more detailed and complex equivalent circuits (Asphahani et al 2008;Thein et al 2010). However, when the same IME-based system is used for different cell types, it is feasible to use the same equivalent circuit to interpret the impedance measurement results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These equivalent circuits have been used to model different types of cells on IMEs or other microelectrodes and for analysis of different impedance components (Ehret et al 1997;). Certainly, microelectrode-based systems for cell attachment could be modeled by more detailed and complex equivalent circuits (Asphahani et al 2008;Thein et al 2010). However, when the same IME-based system is used for different cell types, it is feasible to use the same equivalent circuit to interpret the impedance measurement results.…”
Section: Resultsmentioning
confidence: 99%
“…Our results here only showed a proof-of-concept that the IMEs impedance-based method has the potential to detect oral cancer cells and to distinguish them from noncancer oral epithelial cells. To scale this technique for real sample analysis, the use of well-designed microelectrodes that can perform single cell or a few cells impedance analysis Chen et al 2007;Asphahani et al 2008;Thein et al 2010), and the use of dielectrophoresis or other techniques to collect single cells or a few cells onto each electrode (Gray et al 2004) would be required. In addition, sample pre-treatment, such as depletion of the large number of lymphocyte and normal epithelial cells (Mauk et al 2007), would be needed.…”
Section: Cell Number (Cells) Maxmal Impedance Change At 24 H Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…Varshney and Li showed that the impedance change of Escherichia coli cells is due to the growth and concentration of the cells [17]. Asphahani et al and Panke et al indicated that the adhesion and spreading of cells significantly affect the impedance characteristics obtained using cell-based sensors [18,19]. Hong et al distinguished A549, MDA-MB-231, MCF-7, and HeLa cells using impedance spectra [20].…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4] The impedance value measured with different types of cells such as neural cells, endothelial cells, epithelial cells and cancer cells provides realtime monitoring of cell density, viability, and metabolic activity under a specific culture condition. [5][6][7][8] In real-time monitoring system, the impedance value is detected in direct technique using a pair of sensing and reference electrode submerged in cell culture medium.…”
Section: Introductionmentioning
confidence: 99%